2016
DOI: 10.1002/2016gl070069
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relation between earthquake magnitude and the departure time from P wave similar growth

Abstract: We introduce a new scaling relation between earthquake magnitude (M) and a characteristic of initial P wave displacement. By examining Japanese K‐NET data averaged in bins partitioned by Mw and hypocentral distance, we demonstrate that the P wave displacement briefly displays similar growth at the onset of rupture and that the departure time (Tdp), which is defined as the time of departure from similarity of the absolute displacement after applying a band‐pass filter, correlates with the final M in a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Strong P waves that overlap with weaker S waves represent ongoing energy releases during prolonged ruptures and provide valuable information on rupture development. The possibility that rupture development can be predicted from the initial parts of waveforms is a controversial research topic (e.g., Colombelli et al, ; Hoshiba & Iwakiri, ; Meier et al, , ; Melgar & Hayes, ; Noda & Ellsworth, ; Olson & Allen, ; Rydelek et al, ; Rydelek & Horiuchi, ; Yamada & Ide, ; Zollo et al, ). If rupture processes have nondeterministic characteristics, P waves from growing ruptures are one of the fastest carriers of information on the development of ongoing ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Strong P waves that overlap with weaker S waves represent ongoing energy releases during prolonged ruptures and provide valuable information on rupture development. The possibility that rupture development can be predicted from the initial parts of waveforms is a controversial research topic (e.g., Colombelli et al, ; Hoshiba & Iwakiri, ; Meier et al, , ; Melgar & Hayes, ; Noda & Ellsworth, ; Olson & Allen, ; Rydelek et al, ; Rydelek & Horiuchi, ; Yamada & Ide, ; Zollo et al, ). If rupture processes have nondeterministic characteristics, P waves from growing ruptures are one of the fastest carriers of information on the development of ongoing ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that organization in earthquake complexity permits a sense of determinism whereby observations made in a short period of time at the beginning of an earthquake may be used to infer the overall event size and style (Olson & Allen, 2005;Melgar & Hayes, 2017;Goldberg et al, 2018;Allen & Melgar, 2019). Previous studies have found that early P wave arrivals carry information about the overall earthquake size (Iio, 1995;Beroza & Ellsworth, 1996;Allen & Kanamori, 2003;Olson & Allen, 2005), but such correlations bear large uncertainties that necessitate additional information, such as attenuation parameters, in order to conduct meaningful early magnitude estimation (Wu et al, 2006;Colombelli et al, 2014;Noda & Ellsworth, 2016). The direct P wave arrival, however, represents only a small fraction of the available and potentially deterministic information (Vallée et al, 2017;Vallée & Juhel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has suggested that such structure permits a sense of determinism whereby observations made in a short period of time at the beginning of an earthquake may be used to infer the overall event size and style (1)(2)(3). Previous studies have found that early P waves arrivals inform the overall earthquake size (1, 4), but these correlations bear large uncertainties that necessitate additional information, such as attenuation, for meaningful early magnitude estimate (5)(6)(7). The first P wave arrival, however, represents only a small fraction of potentially 1…”
mentioning
confidence: 99%